Kepastian Hukum Terhadap Keberlakuan Peraturan Menteri Energi Sumber Daya Mineral Nomor 14 Tahun 2024 Dalam Pengurusan Ijin Penggunaan Air Bawah Tanah - Ketut Agus Karmadi; Anak Agung Adi Lestari (Fakultas Hukum, Universitas Mahasaraswati Denpasar, 2026)
This study aims to analyze legal certainty regarding the implementation of Minister of Energy and Mineral Resources Regulation Number 14 of 2024 in the licensing process for groundwater utilization. The regulation of groundwater licensing has undergone significant changes following Law Number 6 of 2023 on Job Creation, which emphasizes simplification and integration of business licensing through the Online Single Submission (OSS) system. This research employs a normative juridical approach using primary legal materials, namely Law Number 17 of 2019 on Water Resources and Ministerial Regulation Number 14 of 2024, supported by relevant secondary literature. The findings indicate that Regulation number 14, 2024 simplifies procedures and integrates licensing mechanisms, including provisions requiring approval from the Ministry of Energy and Mineral Resources for groundwater usage exceeding 100,000 liters per month. However, potential normative ambiguities remain in its implementation. Therefore, strengthened supervision and regulatory harmonization are necessary to ensure legal certainty and sustainable groundwater management.